Effect of dexmedetomidine and midazolam for flexible fiberoptic bronchoscopy in intensive care unit patients: A retrospective study - Gao, Yang (Medicine (Baltimore), 2017)
This study aimed to investigate the clinical effectiveness of dexmedetomidine and midazolam for sedation of intensive care unit (ICU) patients requiring flexible fiberoptic bronchoscopy (FFB). This retrospective cohort study included 148 patients from the third ICU ward of the Second Affiliated Hospital of Harbin Medical University (Harbin, China) who received simultaneous invasive mechanical ventilation and FFB between March 2012 and December 2014. Patients were divided into dexmedetomidine (n  =  72) and midazolam (n  =  76) groups according to sedative mode. The sedative effects, incidence of adverse events, and bronchoscopist satisfaction scores were compared between groups. During FFB, total sedation time and total time of FFB were significantly shorter in the midazolam group (P < .001, respectively), with a lower percentage of these patients requiring propofol for remedial sedation (P < .001). The incidence of FFB-related adverse events (including bronchospasm, cough, and decreased oxygen saturation) was significantly higher in dexmedetomidine group compared with midazolam group (P  =  .007, .014 and .008, respectively). However, the incidence of other adverse events was not significantly different between groups. In addition, bronchoscopist satisfaction scores were significantly higher in the midazolam compared with dexmedetomidine group (7.72 ± 1.65 vs 7.08 ± 1.77; P  =  .030). For sedation of ICU patients during FFB, combination of midazolam and dexmedetomidine demonstrated an enhanced sedative effect, lower incidence of adverse events, and higher bronchoscopist satisfaction score compared with dexmedetomidine alone, thus represents a suitable alternative sedative for FFB patients.